LO60: Frailty and associated prognosis among older emergency department patients with suspected infection – a prospective, observational cohort study. (May 2020) - Fernando, S.; Guo, K.; Lukasik, M.; Rochwerg, B.; Cook, D.; Kyeremanteng, K.; Perry, J.
Abstract : Introduction: Prognostication and disposition among older Emergency Department (ED) patients with suspected infection remains challenging. Frailty is increasingly recognized as a predictor of poor prognosis among critically ill patients, however its association with clinical outcomes among older ED patients with suspected infection is unknown. Methods: We conducted a multicentre prospective cohort study at two tertiary care EDs. We included older ED patients (≥ 75 years) presenting with suspected infection. Frailty at baseline (prior to index illness) was explicitly measured for all patients by the treating physicians using the Clinical Frailty Scale (CFS). We defined frailty as a CFS 5-8. The primary outcome was 30-day mortality. We used multivariable logistic regression to adjust for known confounders. We also compared the prognostic accuracy of frailty against the Systemic Inflammatory Response Syndrome (SIRS) and Quick Sequential Organ Failure Assessment (qSOFA) criteria. Results: We enrolled 203 patients, of whom 117 (57.6%) were frail. Frail patients were more likely to develop septic shock (adjusted odds ratio [aOR]: 1.83, 95% confidence interval [CI]: 1.08-2.51) and more likely to die within 30 days of ED presentation (aOR 2.05, 95% CI: 1.02-5.24). Sensitivity for mortality was highest among the CFS (73.1%, 95% CI: 52.2-88.4), as compared to SIRS ≥ 2 (65.4%, 95% CI: 44.3-82.8) or qSOFA ≥ 2 (38.4, 95% CI: 20.2-59.4). Conclusion: Frailty is a highly prevalent prognostic factor that can be used to risk-stratify older ED patients with suspected infection. ED clinicians should consider screening for frailty in order to optimize disposition in this population.